Seismic Response Analysis of 2-Storey Mosque Structure Using Diagonal Brace Damper and Toggle Brace Damper - Julian Fikri; Li-Jeng Huang (International Journal of Research in Vocational Studies (IJRVOCAS), 2022)
Mosque structure are typical public building where Muslim follower doing their worship and social activities. These structures are common in Indonesia where the dangerous earthquake usually happens. This paper is aimed to study of passive control of a typical 2-storey Mosque structure using diagonal and toggle brace damper. At the first, we build a simplified structure model of 2 degree of freedom (2DOF) for controlled and uncontrolled system. In this study, we create 5 cases where case 1 as uncontrolled system. Then we compared the dynamic responses of the structure cases subjected to 1940 El Centro earthquake record using time history analysis (THA). The effect of the geometric configuration of the damper attached to the structure which influenced by the magnification factor will be studied.